Hypersensitivity reactions to small molecule drugs - Han, Jiayin; Pan, Chen; Tang, Xuan; Li, Qi; Zhu, Yan; Zhang, Yushi; Liang, Aihua (Frontiers in Immunology, 2022)
Drug hypersensitivity reactions induced by small molecule drugs encompass a broad spectrum of adverse drug reactions with heterogeneous clinical presentations and mechanisms. These reactions are classified into allergic drug hypersensitivity reactions and non-allergic drug hypersensitivity reactions. At present, the hapten theory, pharmacological interaction with immune receptors (p-i) concept, altered peptide repertoire model, and altered T-cell receptor (TCR) repertoire model have been proposed to explain how small molecule drugs or their metabolites induce allergic drug hypersensitivity reactions. Meanwhile, direct activation of mast cells, provoking the complement system, stimulating or inhibiting inflammatory reaction-related enzymes, accumulating bradykinin, and/or triggering vascular hyperpermeability are considered the main factors causing non-allergic drug hypersensitivity reactions. To date, many investigations have been performed to explore the underlying mechanisms involved in drug hypersensitivity reactions and to search for predictive and preventive methods in both clinical and nonclinical trials. However, validated methods for predicting and diagnosing hypersensitivity reactions to small molecule drugs, as well as deeper insight into the relevant underlying mechanisms, are still limited.